P625 Trends in symptomatic presentation among reported gonorrhea cases, STD surveillance network (SSuN), 2010–2017. (14th July 2019) - Stenger, Mark; Weston, Emily; Amiya, Rachel; Han, Emily; Kerani, Roxanne; Klingler, Ellen; Kohn, Robert; Nguyen, Trang; Schumacher, Christina; Torrone, Elizabeth
Abstract : Background: Rates of reported gonorrhea cases have increased in recent years among all groups in the U.S. Expanded screening, particularly extragenital screening among men who have sex with men (MSM), results in increased case finding, complicating interpretation of reported case rates. Monitoring trends in symptomatic presentation through enhanced surveillance may provide insight into changes in case rates. Methods: Randomly sampled cases from 54 counties in 5 U.S. states 2010–2017 were interviewed; symptom status (patient report of 'any STD symptoms') and sex-of-sex partner(s) were elicited. Interviewed cases were weighted to be representative of all reported cases in participating jurisdictions. Proportion of cases presenting with symptoms and symptomatic rate per 100, 000 were calculated, stratified by gender and sex-of-sex partners. Trends over time were evaluated by Cochran-Armitage and Pearson's trend tests. Results: During 2010–2017, 21, 006 cases were interviewed, representing over 500, 000 reported cases. Symptom status was available for 97.1%; the estimated number of symptomatic cases increased 125.9% (30, 883 to 69, 772). The proportion of women and non-MSM males reporting symptoms increased by 15.3% (48.3% to 55.7%) and 11.5% (80.1% to 89.3%), respectively. Conversely, the proportion of MSM cases reporting symptoms decreased by 23.2% (72.5% to 55.7%). Relative increase in estimated symptomatic case rate from 2010 to 2017 was 82.8% among women (56.0 to 102.4 per 100, 000), 82.8% among non-MSM males (67.0 to 122.5 per 100, 000) and 185.9% among MSM (946.2 to 2705.2 per 100, 000). All trends were significant at p<0.05. Conclusion: Decreases in the proportion of MSM cases reporting symptoms suggests increased case rates among MSM are partially attributable to expanded screening. Yet a significant, increasing trend in the symptomatic case rate among MSM suggests a real increase in gonorrhea transmission. The proportion symptomatic and symptomatic case rates for non-MSM males and females are also rising, suggesting more transmissions in these groups as well. Disclosure: No significant relationships.